Modeling hourly diffuse solar-radiation in the city of São Paulo using a neural-network technique - Soares, J.; Oliveira, A. P.; Boznar, M. Z.; Mlakar, P.; Escobedo, João Francisco [UNESP]; Machado, A. J. (Elsevier B.V., 2004)
dIn this work, a perceptron neural-network technique is applied to estimate hourly values of the diffuse solar-radiation at the surface in São Paulo City, Brazil, using as input the global solar-radiation and other meteorological parameters measured from 1998 to 2001. The neural-network verification was performed using the hourly measurements of diffuse solar-radiation obtained during the year 2002. The neural network was developed based on both feature determination and pattern selection techniques. It was found that the inclusion of the atmospheric long-wave radiation as input improves the neural-network performance. on the other hand traditional meteorological parameters, like air temperature and atmospheric pressure, are not as important as long-wave radiation which acts as a surrogate for cloud-cover information on the regional scale. An objective evaluation has shown that the diffuse solar-radiation is better reproduced by neural network synthetic series than by a correlation model. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: hourly diffuse solar radiation; perceptron neural network; São Paulo City